Analysis of Students’ Level of Environmental Literacy on Waste Management as An Effort for Green Behavior in East Jakarta Islamic Boarding School - Sanjayanti, Arum; Fauzi, Ferry (Universitas Sembilanbelas November Kolaka, 2024)
The abundance of waste is a serious problem in Indonesia, especially in Islamic boarding school environments. Waste management in general has been carried out. Still, it has not been actively promoted, and there is a lack of knowledge about minimizing the negative impact of waste in the Islamic boarding school environment even though they have previously received counseling about environmental literacy. This research aims to analyze the level of ecological literacy in waste management. The research method uses a qualitative descriptive method. The test instrument uses essay questions, and the non-test uses observations and interviews with teachers and school principals. The population of this study was all class X enrolled at one of the Islamic boarding schools. The sample was determined using a purposive sampling technique. The research sample consisted of 30 students in the even semester of 2023/2024. The research results show that waste management environmental literacy skills are in the